People living with psychosocial disability: Rehabilitation and recovery-informed service provision within the second Australian national survey of psychosis. (June 2016) - Harvey, Carol; Brophy, Lisa; Parsons, Samuel; Moeller-Saxone, Kristen; Grigg, Margaret; Siskind, Dan
Objective: People with psychosocial disability are an important, although often neglected, subgroup of those living with severe and persistent mental illness. Rehabilitation, provided through clinical and non-government organisations in Australia, may contribute to their personal recovery goals. We hypothesised that people with psychoses with the greatest disability and complex needs would receive services from both sectors, reflecting treatment and rehabilitation needs. Method: Participants in the 2010 Australian national survey of psychosis ( n = 1825) were interviewed to assess demographic, functional, mental and physical health characteristics and service use in the previous year. Two subgroups were created and compared: those using services from community mental health with, and without, non-governmental organisation involvement. Group membership was predicted by hierarchical logistic regression using variables selected on a priori grounds. Usefulness of the final model was examined by calculating improvement over the rate of accuracy achievable by chance alone. Results: The model was statistically significant but fell just short of useful (criterion 71.6%, model achieved 70.6%). Four independent variables contributed uniquely to predicting whether participants received both services (never married, childhood trauma, group accommodation, poor global functioning) consistent with the hypothesis. However, severe dysfunction in socialising was less likely to predict membership of the combined services group when compared with no dysfunction ( p = 0.001, odds ratio = 0.384, confidence interval = [0.218, 0.677]), as was current smoking compared with none ( p = 0.001, odds ratio = 0.606, confidence interval = [0.445, 0.824]). Conclusion: Findings suggest services provided by non-governmental organisations are targeted to those with the greatest disability although targeting could be improved. A subgroup of people with psychosis and severe disability in community mental health services do not access non-governmental services. Their unmet needs for rehabilitation and recovery have important implications for future development of community mental health, including the non-governmental sector.